Analisis Miskonsepsi Pada Soal Cerita Teori Peluang Di Program Studi Pendidikan Matematika - Jitu Halomoan Lumbantoruan; Hendrikus Male (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
In this study the background to the problem is the low student learning outcomes in the Theory of Opportunities course. Opportunity theory is a course where students must master terminology, concepts, principles, algorithms and languages ??or the essence of a story problem. To be able to solve mathematical story problems, it is obligatory to master the five components. The purpose of this study is to determine where misconceptions are often experienced by students in understanding the essence and problem solving of probability theory stories, as well as any factors that hinder the learning process of opportunity theory courses outside the five components. The research subjects taken were mathematics education students in the odd semester of the 2018/2019 school year. Data collection techniques and methods used are the method of observation, interviews, documentation, and tests. The results of this study indicate that there are 41% do not master the terminology, the concept of 44.7%, prinsisp 47.8%. Algorithm 51%, and language / conclusion drawing 52%. There were 12 questions that were tested and the average student who could answer haya was around 51% and those who were still experiencing misconceptions were 49%. Algorithm and conclusion drawing are one where many students experience misconceptions in solving the problem story theory questions. Keywords : Misconception of probability theory, Misconception Analysis